Prosthetic Treatment Needs among Institutionalized Elderly in Baghdad - Iraq (Mustansiria Dental Journal, 2018)
This study was used to investigate the oral health status and treatment needs in elderly patients having a pattern of chronic general diseases that often result in social disadvantage. The study sample consisted of seventy patient admitted to the elderly institution. Standardized dental probes and mirrors were used for the clinical examination; questionnaires were taken from elderly patients. The results of this study indicated that the prosthetic treatment was needed in 45 patient which equal to (64.3%) of total. Relining of the dentures was considered sufficient treatment in about (25%) of the patients weaning dentures, while constructing of new dentures were necessary for four patients. The dental health service programs for geriatric patients should be improved and carried out in connection with their institution